Provision of Contraception Equipment Education through Leaflet Media for Normal Postpartum Women at Hj Regional Hospital, Anna Lasmanah Banjarnegara - Agus Hari Sandika; Anastasia Chrissanti; Tin Utami; Resti Putranti (LPPM Universitas Harapan Bangsa, 2023)
The Indonesian Nursing Diagnostic Standard (IDHS) lists readiness to improve knowledge, which is defined as the cognitive development of information on a particular topic to meet health goals, as a problem in nursing that can be demonstrated by asking the content of the topic, expressing interest in learning, and behaving in accordance with the knowledge according to the topic. A sample of one child of childbearing age after normal (spontaneous) delivery was used in the descriptive design of this case study, and a nursing care approach that included assessment, diagnosis, nursing planning, implementation, evaluation, and analysis was used. Methods: nursing care data collection techniques which include interviews, documentation, observation and health promotion through leaflet media. Results: nursing diagnoses that emerged were readiness to increase knowledge where after 2 days of nursing activities, the results of the first and second day evaluations were resolved according to the recommended behavioral indicators and criteria, increased, knowledge of the importance of birth control and contraceptive methods increased, erroneous perception of a problem decreased. Conclusion: there is an effectiveness of the results of the application of nursing care with health education interventions through leaflet media that increases the level of knowledge for Mrs.S with the safest percentage of birth control types, namely spirals.